Electroretinogram b/a wave ratio improvement in central retinal vein obstruction. Issue 3 (March 1994) - Matsui, Y; Katsumi, O; Sakaue, H; Hirose, T
Abstract : The electroretinogram (ERG), especially the b/a wave ratio, is considered a good indicator of retinal ischaemia in central retinal vein obstruction (CRVO). Seven CRVO patients who showed b/a wave ratio improvement from < 1.0 [negative type (-) ERG] to > or = 1.0 and one from 1.07 to 1.53 were studied. Three mechanisms of change were observed: firstly, the b-wave amplitude increased without an a-wave amplitude decrease (group A, n = 2); secondly, the b-wave amplitude increased with an a-wave amplitude decrease (group B, n = 4); and, thirdly, both decreased, but the a-wave amplitude decreased more markedly (group C, n = 2). In group A, the visual acuities improved markedly. In group B, the visual acuities improved in two cases in which the b-wave amplitude reached the normal range; the visual acuities did not improve in two cases in which the b-wave amplitude did not reach the normal range. In group C, the visual acuities remained poor. The negative (-) ERG or significantly reduced b/a wave ratio is associated with ischaemic CRVO and did not occur because of the filtering effect of the haemorrhage, which may reduce the stimulus light for the ERG. Improvement of the reduced b/a wave ratio with an increased b-wave amplitude was accompanied by improvements in fundus appearance and visual acuity in CRVO. The results suggest that the retinal ischaemia in CRVO, as revealed by the ERG and fluorescein angiogram, may be reversible in some cases.